Intestinal permeability, food antigens and the microbiome: a multifaceted perspective - Valitutti, Francesco; Mennini, Maurizio; Monacelli, Gianluca; Fagiolari, Giulia; Piccirillo, Marisa; Di Nardo, Giovanni; Di Cara, Giuseppe (Frontiers in Allergy, 2025)
The gut barrier encompasses several interactive, physical, and functional components, such as the gut microbiota, the mucus layer, the epithelial layer and the gut mucosal immunity. All these contribute to homeostasis in a well-regulated manner. Nevertheless, this frail balance might be disrupted for instance by westernized dietary habits, infections, pollution or exposure to antibiotics, thus diminishing protective immunity and leading to the onset of chronic diseases. Several gaps of knowledge still exist as regards this multi-level interaction. In this review we aim to summarize current evidence linking food antigens, microbiota and gut permeability interference in diverse disease conditions such as celiac disease (CeD), non-celiac wheat sensitivity (NCWS), food allergies (FA), eosinophilic gastrointestinal disorder (EOGID) and irritable bowel syndrome (IBS). Specific food elimination diets are recommended for CeD, NCWS, FA and in some cases for EOGID. Undoubtfully, each of these conditions is very different and quite unique, albeit food antigens/compounds, intestinal permeability and specific microbiota signatures orchestrate immune response and decide clinical outcomes for all of them.